Bacterial contamination of platelet concentrates stored at 20°C. Issue 6 (June 1973) - Cunningham, Margaret; Cash, John D.
Abstract : Qualitative and quantitative data on the bacterial contamination of 1000 platelet concentrates prepared and stored at 20°C are presented. Using cooked meat medium the incidence of contamination was 6·3%. However, nutrient agar platelet counts showed the concentration of bacteria to be low. The clinical significance of these results is discussed.